The abject lover of the Courtly Love Era - Halimah Mohamed Ali, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
This essay discusses the courtly love era through the work of Samuel Daniel with reference to his sonnet sequence To Delia. The discussion is varied using the psychoanalysis lens proposed by Jacque Lacan and Julia Kristeva. It defines what courtly love is and how court poetry is used to woo the lady. The discussion defines love and sexual desire that is portrayed through the sonnets. It is concluded that the persona’s flattery of the lady as well as verbal threats laced with the use of metaphors culminate in elevating his own self rather than the lady he is wooing.